Perbaikan Manajemen Reproduksi Sapi Potong Peternakan Rakyat di Kecamatan Pakis - Sholikah, Nisa'us; Sumartono (Jurnal Pemberdayaan Masyarakat, 2021)
Beef cattle are ruminants that have economic value for people's lives in rural areas. The problem that is often faced by beef cattle farmers is the farmer's knowledge that is still lacking because they still rely on experience without being based on correct and precise technical knowledge. The aim of the program was to increased the knowledge of traditional farmers about reproductive management so as to increase the productivity of beef cattle. The target audience for this activity was traditional farmers who maintain productive female beef cattle in Pakis Subdistrict. The method used in the community service program was counseling on reproduction management and application of recording. The results of this community service activity are manifested in an increase in the knowledge of traditional farmers in Pakis Subdistrict and the motivation to improve the management of the reproduction of beef cattle being raised based on the analysis of the results of the pre-test and post-test. It is hoped that the improvement of reproductive management can help increase productivity and improve the economy of traditional farmers if it is implemented correctly and appropriately.